Metodología de inspección, mejora en procesos constructivos a través de la PMBOK (2020)
The following document shows how there are inspection methodologies that can improve construction processes through a compendium of foundations established by PMBOK that can be standardized and controlled in such a way that they allow us continuous improvement; adapting the principles to different construction projects in all execution processes. In this document we can recreate a service or a product of a very high level in terms of quality if it is possible to compromise the effort of a work team; This text aims to improve quality standards, costs, and established times, but with monitoring commitments that allow adjustments to be made before, during and at the completion of a project under construction.